Alterations in Alzheimer's disease microglia transcriptome might be involved in bone pathophysiology - Mohini Gharpure; Sagar Vyavahare; Pankaj Ahluwalia; Sonu Kumar Gupta; Tae Jin Lee; Jayant Lohakare; Ravindra Kolhe; Yun Lei; Ferenc Deak; Xin-Yun Lu; Carlos M. Isales; Sadanand Fulzele (Neurobiology of Disease, 2024)
Aging is a major risk factor for multiple chronic disorders in the elderly population, including Alzheimer's disease (AD) and Osteoporosis. AD is a progressive neurodegenerative disease characterized by memory loss. In addition to dementia, several studies have shown that AD patients experience an increased rate of musculoskeletal co-morbidities, such as osteoporosis. Since tissue-specific macrophages contribute to both diseases, this study analyzed the microglia transcriptome of AD mice to determine a common gene signature involved in osteoclast biology. After comparing differentially regulated genes from GEO data sets (GSE93824 and GSE212277), there were 35 common upregulated genes and 89 common downregulated genes. Of these common genes, seven genes are known to play an important role in bone homeostasis. CSF1, SPP1, FAM20C, and Cst7 were upregulated and are associated with osteoclastogenesis and inflammation. Among the downregulated genes, LILRA6, MMP9, and COL18A1 are involved in bone formation and osteoclast regulation. We further validated some of these genes (CSF1, Cst7, and SPP1) in the cortex and the bone of AD mice models. The dysregulation of these microglial genes in AD might provide insights into the co-occurrence of AD and osteoporosis and offer potential therapeutic targets to combat disease progression.